The Effectiveness Of Deoderatex Membrane Treatment Of Odour At Toilet In Vertical Application - Abd Rahim, Siti Aini Nabilah (Universiti Sains Malaysia, 2018)
One of the mainly discussed environmental issues the odour pollution. The presence of odour existing in the campus especially in the toilet due to the daily activity of the toilet; urine and faeces, animal waste and food waste was identified through observation and survey conducted to the user. However, none of the study is conducted to control the odour problem in the toilet except the daily cleaning of the toilet by the cleaner. The good condition after cleaning cannot last long due to continuous usage of the toilet. So, this study is conducted to control odour in the toilet and provide a comfortable usage of toilet to the user for a longer time by using odour removing membarane “Deodoratex”. This study is conducted by using two different types of Deodoratex ; Type 03 and Type 32 and each of the type will be used to identified 3 types of gas concentration in the toilet; Odour, Ammonia and Hydrogen Sulfide. This concentration will be obtained by using SM100 Field Olfactometer and TR8 Odotracker through field assessment. In addition, this study also conducted to identify the effectiveness of the different type of Deodoratex to remove the concentrations in vertical application. The Type 03 Deodoratex is more effective to remove odour when hung vertically.